Time‐restricted eating, caloric reduction, and unrestricted eating effects on weight and metabolism: a randomized trial - Niki C. Oldenburg; Douglas G. Mashek; Lisa Harnack; Qi Wang; Emily N. C. Manoogian; Nicholas G. Evanoff; Donald R. Dengel; Abdisa Taddese; Brad A. Yentzer; LESIA F. LYSNE; Alison Wong; Michelle J. Hanson; et al. (2025)
Metabolic improvements may precede weight loss. We compared the effects of self-selected 8-h time-restricted eating (TRE), 15% caloric restriction (CR), and unrestricted eating (UE) on weight, body composition, caloric intake, glycemic measures, and metabolic flexibility. In this 12-week randomized-controlled trial, we measured weight (primary outcome), body composition (dual-energy x-ray absorptiometry/magnetic resonance imaging), caloric intake (24-h recall), metabolic flexibility (indirect calorimetry during hyperinsulinemic-euglycemic clamp), and glycemic measures (hemoglobin A1c, hyperinsulinemic-euglycemic clamp, continuous glucose monitoring). Of the 88 enrolled participants, 81 (92%) completed the trial (mean [SD], age, 43.2 [10.5] years, BMI, 36.2 [5.1] kg/m2; 54.5% female, 84.1% White). Final eating windows were 9.8 h (95% CI: 9.0 to 10.6) for TRE, 12.9 h (95% CI: 11.9 to 13.9) for CR, and 11.8 h (95% CI: 11.0 to 12.7) for UE. Compared with UE (n = 29), weight changes were -1.4 kg (95% CI: -4.5 to 1.7; p = 0.53) with TRE (n = 30) and -2.5 kg (95% CI: -5.8 to 0.8; p = 0.18) with CR (n = 29). TRE showed lower metabolic flexibility than CR (-0.041 [95% CI: -0.080 to -0.002]). Weight, body composition, caloric intake, and glycemic measures were similar among groups. Eating window reduction correlated with decreased caloric intake and visceral fat. In a 12-week intervention, TRE did not lead to significant improvements in weight, average body composition, or glycemic or metabolic measures compared with CR or UE.